2021
DOI: 10.1002/brb3.2270
|View full text |Cite
|
Sign up to set email alerts
|

Is there collaboration specific neurophysiological activation during collaborative task activity? An analysis of brain responses using electroencephalography and hyperscanning

Abstract: Collaboration between two individuals is thought to be associated with the synchrony of two different brain activities. Indeed, prefrontal cortical activation and alpha frequency band modulation has been widely reported, but little is known about interbrain synchrony (IBS) changes occurring during social interaction such as collaboration or competition. In this study, we assess the dynamic of IBS variation in order to provide novel insights into the frequency band modulation underlying collaboration. To addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…In line with the EEG-hyperscanning literature on cooperative vs. competitive joint actions, we employed a zero-lag-insensitive, phase synchrony-based approach. Previous studies have usually employed the phase locking value (PLV) to estimate the phase synchronization between two EEG signals in the comparison between cooperation and competition [34][35][36]. Liu and colleagues (2021) [34] and Sinha and colleagues (2016) [35] did not obtain significant results, whereas Léné and colleagues (2021) [36] succeeded in differentiating cooperation from competition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with the EEG-hyperscanning literature on cooperative vs. competitive joint actions, we employed a zero-lag-insensitive, phase synchrony-based approach. Previous studies have usually employed the phase locking value (PLV) to estimate the phase synchronization between two EEG signals in the comparison between cooperation and competition [34][35][36]. Liu and colleagues (2021) [34] and Sinha and colleagues (2016) [35] did not obtain significant results, whereas Léné and colleagues (2021) [36] succeeded in differentiating cooperation from competition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have usually employed the phase locking value (PLV) to estimate the phase synchronization between two EEG signals in the comparison between cooperation and competition [34][35][36]. Liu and colleagues (2021) [34] and Sinha and colleagues (2016) [35] did not obtain significant results, whereas Léné and colleagues (2021) [36] succeeded in differentiating cooperation from competition. However, it must be noted that Léné and colleagues did not use an ecological study paradigm, but a computer-based fast button-response task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the original study, we examined whether IBS was specific to the interacting pair. One of the pitfalls of hyperscanning is that an increased IBS might be observed when a different participant performs the same task independently, although there is no interaction between pairs [ 18 ]. Therefore, we confirmed that IBS would be higher in interacting pairs than in non-interacting pairs by performing random-pair analysis.…”
Section: Introductionmentioning
confidence: 99%